2021
DOI: 10.1101/2021.02.11.430640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute stress blunts prediction error signals in the dorsal striatum during reinforcement learning

Abstract: Reinforcement learning, which implicates learning from the rewarding and punishing outcomes of our choices, is critical for adjusted behaviour. Acute stress seems to affect this ability but the neural mechanisms by which it disrupts this type of learning are still poorly understood. Here, we investigate whether and how acute stress blunts neural signalling of prediction errors during reinforcement learning using model-based functional magnetic resonance imaging. Male participants completed a well-established r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 69 publications
0
6
1
Order By: Relevance
“…However, in both studies, effectiveness of stressor was only confirmed with subjective ratings instead of physiological correlate such as cortisol or heart rate. Furthermore, the nature of stressors in both studies, namely, uncontrollable sounds (Carvalheiro et al, 2021) and threat of shock (Robinson et al, 2013), differs from our focus on psychosocial stress. Although both studies employed reward‐learning paradigms, they did not tap reversal learning specifically.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, in both studies, effectiveness of stressor was only confirmed with subjective ratings instead of physiological correlate such as cortisol or heart rate. Furthermore, the nature of stressors in both studies, namely, uncontrollable sounds (Carvalheiro et al, 2021) and threat of shock (Robinson et al, 2013), differs from our focus on psychosocial stress. Although both studies employed reward‐learning paradigms, they did not tap reversal learning specifically.…”
Section: Introductionmentioning
confidence: 84%
“…The few studies using within‐subjects designs to investigate learning are either purely behavioural (Radenbach et al, 2015) focused on psychoimmunological measures (Treadway et al, 2017) or neuroimaging methods such as electroencephalography (Cavanagh et al, 2011), which lacks the possibility of precise spatial signal localization and anatomical specificity with respect to the neural representation of RPE signals. To our knowledge, only two studies combine a within‐subjects design with computational modelling and functional neuroimaging (fMRI) to elucidate underlying cognitive mechanisms (Carvalheiro et al, 2021; Robinson et al, 2013). However, in both studies, effectiveness of stressor was only confirmed with subjective ratings instead of physiological correlate such as cortisol or heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of acute stress on punishment learning are generally less well-understood (Porcelli & Delgado, 2017). Previous behavioral studies suggest that acute stress impairs reward learning, but the evidence for stress-induced deficits in punishment learning is scarcer (Berghorst et al, 2013;Carvalheiro et al, 2021aCarvalheiro et al, , 2021bPorcelli & Delgado, 2017). Reward learning has been robustly associated with dopaminergic functioning (Daw & Tobler, 2014;Glimcher, 2011;Pessiglione et al, 2006;Schultz et al, 1997), and it is known that acute stress increases dopamine release (Adler et al, 2000;Cabib & Puglisi-Allegra, 2012;Pruessner et al, 2004), which in turn might affect this type of learning.…”
Section: Discussionmentioning
confidence: 99%
“…Acute stress, albeit ubiquitous in everyday life, is known to impact reinforcement learning in healthy individuals (Porcelli & Delgado, 2017). Accumulating evidence suggests that acute stress impairs reward learning (Berghorst et al, 2013;Bogdan & Pizzagalli, 2006;Bogdan et al, 2011;Carvalheiro et al, 2021aCarvalheiro et al, , 2021bCremer et al, 2021;de Berker et al, 2016;Morris & Rottenberg, 2015;Paret & Bublatzky, 2020) and punishment learning (de Berker et al, 2016;Petzold et al, 2010), although the evidence for the latter is less robust (Aylward et al, 2019;Carvalheiro et al, 2021aCarvalheiro et al, , 2021bPorcelli & Delgado, 2017). Previous research indicates that individuals with high levels of psychopathic traits present blunted stress reactivity (Cima et al, 2008;Holi et al, 2006;House & Milligan, 1976;Johnson et al, 2015;Lidberg et al, 1978;Loney et al, 2006).…”
mentioning
confidence: 99%
“…Better than expected outcomes elicit positive prediction errors, while worse than expected outcomes elicit negative prediction errors, thus updating estimated action values to support optimal choices (Rigoli et al, 2016;Schultz, 2016;Schultz et al, 1997). Stress can interfere with this learning process, damaging reward maximization (Berghorst et al, 2013;Carvalheiro et al, 2021a;2021b;de Berker et al, 2016;Morgado et al, 2015;Pizzagalli, 2014;Starcke & Brand, 2012;Voulgaropoulou et al, 2021) and impairing avoidance of aversive outcomes (Raio et al, 2017). For example, anticipating threat of shock impairs performance in probabilistic reward learning tasks (Bogdan et al, 2011;Bogdan & Pizzagalli, 2006;Paret & Bublatzky, 2020), and acute stress dampens neural activation associated with reward sensitivity in ventromedial prefrontal cortex (vmPFC) and dorsal striatum (Porcelli et al, 2012).…”
mentioning
confidence: 99%